Surface and interface engineering for highly efficient Cu2ZnSnSe4 thin-film solar cells via in situ formed ZnSe nanoparticles. Issue 9 (4th February 2021) - Yoo, Hyesun; Park, Jongsung; Suryawanshi, Mahesh P.; Lee, Jiwon; Kim, JunHo; Eom, Kiryung; Seo, Hyungtak; Jung, HyoRim; Kim, Dong Myeong; Shin, Seung Wook; Kim, Jin Hyeok
Abstract : In situ formed ZnSe NPs on the surface of CZTSe offer surface and interface engineering and provide a favourable band alignment between CZTSe and CdS leading to an improved device efficiency of 10.49%. Abstract : Kesterite surface properties and band alignment behavior at an absorber/buffer interface are key issues for highly efficient kesterite solar cell devices. Herein, we report new insights into surface and interface engineering and favorable band alignment of Cu2 ZnSnSe4 (CZTSe)/CdS buffer in solar cells via in situ formed ZnSe nanoparticles (NPs) on the CZTSe surface. The device characteristics and junction qualities of the CZTSe solar cells with in situ formed ZnSe NPs are improved even though they have similar bulk properties to CZTSe thin films. X-ray photoelectron spectroscopy (XPS) characterization revealed a favorable conduction band offset (CBO, +0.26 eV) for CZTSe/ZnSe NPs/CdS compared to that for CZTSe/CdS (+0.01 eV) and CZTSe/ZnSe layer/CdS (+0.976 eV), respectively. In this regard, we also postulated a formation mechanism for in situ formed ZnSe NPs on the CZTSe surface via annealing of metallic precursors with different stacking orders. This work offers a simple and source-free interface engineering strategy using in situ formed ZnSe NPs (secondary phase) on the CZTSe surface to further improve the performance of kesterite solar cell devices.